The functions of public administration - Бородін, Іван Лук'янович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
In the article attention was paid to the fact that process of public administration is reflected through a combination of functions. Being interdependent and interrelated functions of public administration are one whole. Their analysis gives the possibility to understand the peculiarities of relations of subjects of public administration. It is reported that they are realized through the forms and methods of public administration, that show ways and means of the process of public administration. The article proposes their systematization. The main idea of the article is that administrative service is the separate function of public administration